Challenging the inevitable: Anatomy of a Suicide at the Royal Court Theatre London - Rayner, Francesca (2018)
[Extract] As the title suggests, this performance was not for the faint-hearted. In another collaboration with director Katie Mitchell following the 2015 Ophelia’s Zimmer, playwright Alice Birch has written a remarkable piece about inherited suicide along the maternal line.[...]